2020
DOI: 10.1002/admi.201901864
|View full text |Cite
|
Sign up to set email alerts
|

Domino P‐µMB: A New Approach for the Sequential Immobilization of Enzymes Using Polydopamine/Polyethyleneimine Chemistry and Microfabrication

Abstract: Developing a facile approach for the manipulation of the direction and order of the enzymatic reactions via sequential immobilization on inexpensive substrates is a continuous demand. Herein, a new methodology is introduced that allows making a desired enzymatic reaction pathway on a paper‐based microfluidic‐membrane based biosensor (P‐µMB). Although the method is universal, here, as a proof‐of‐concept, the sequential immobilization of α‐amylase, glucose oxidase (GOx) and horseradish peroxidase (HRP) is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The major mechanism for this is that dopamine self-polymerizes and forms PDA when the catechol group is oxidized to o -quinone under oxidizing conditions and then deposited on the surface of a substance . In recent years, many studies have developed a variety of dopamine-based coatings through co-deposition strategies for use in more applications. Among them, polyethyleneimine (PEI) is a popular polymer used to prepare hybrid coatings. ,, Since PEI can be deposited on a surface through the formation of covalent bonds with oxidized dopamine via the Michael addition and Schiff base reaction, the incorporation of PEI can destroy the noncovalent interactions in PDA (such as hydrogen bonds and π–π stacking) to reduce the PDA aggregations and make the deposited coating uniform. A previous study indicated that the addition of PEI significantly accelerated the deposition process, so the deposition time is greatly shortened .…”
Section: Introductionmentioning
confidence: 99%
“…The major mechanism for this is that dopamine self-polymerizes and forms PDA when the catechol group is oxidized to o -quinone under oxidizing conditions and then deposited on the surface of a substance . In recent years, many studies have developed a variety of dopamine-based coatings through co-deposition strategies for use in more applications. Among them, polyethyleneimine (PEI) is a popular polymer used to prepare hybrid coatings. ,, Since PEI can be deposited on a surface through the formation of covalent bonds with oxidized dopamine via the Michael addition and Schiff base reaction, the incorporation of PEI can destroy the noncovalent interactions in PDA (such as hydrogen bonds and π–π stacking) to reduce the PDA aggregations and make the deposited coating uniform. A previous study indicated that the addition of PEI significantly accelerated the deposition process, so the deposition time is greatly shortened .…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] Therefore, a broad range of biomaterials has been exploited, which commonly include natural or synthetic hydrogels, 28 electrospun polymeric fibers, 29 and patterned plastic or glass-based substrates. In particular, paper-based cell culture platforms have become increasingly popular for in vitro expansion of cells as well as biomedical applications, like designing anti-biofouling membranes, 30 biosensors, 31,32 tissue regeneration, drug screening, and disease modeling. 33 The biocompatibility, porous and flexible structure, low-cost, and easy high-throughput manufacturing make paper scaffolds the ideal subjects for construction of complex tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The abovementioned results are of great interest due to the effective and complete removal of crystal violet dye through a heterogeneous system. The removal of crystal violet dyes in the system attributed to the synergistic effect involves a multistep reaction which led to the generation of highly reactive • OH radicals followed by oxidation of crystal violet dye into nontoxic substances . Based on that, the plausible underlying mechanism of removal of crystal violet dye in a bio-Fenton system using GOx-immobilized fibrous catalysts has been postulated.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies demonstrated that a tailor-made surface of support material with a specific functionality may enhance the efficiency of enzyme immobilization. ,, A higher density of amine functional groups in the surface of polyester textile may open the possibility of higher enzyme loading (more binding sites to immobilize additional enzymes over the surface) and robust immobilization (single enzyme may interact with the multiple points of support materials). Schnapp and Shalitin (1976) reported that amine groups carrying materials can be readily linked to enzymes due to the characteristic affinity of amine groups toward proteins/enzymes which has been supported by some other reports. Although interaction of amine functional groups with enzymes is well-matured in other domains, but to our best knowledge, there has been no effort given to the avenue in the domain of textile biotechnology in relation to tailoring the polyester textile through integrating amine-rich polymers for immobilization of enzymes. Therefore, this study apprehends the tailoring of the surface of polyester textile through either plasma eco-technology (activation) in the presence of O 2 /N 2 gas and/or chemical grafting of bio-based chitosan (CS) and polyethylenimine (PEI, two well-known polymers having primary amino terminal groups) before immobilizing the glucose oxidase (GOx) enzyme through the physical adsorption method.…”
Section: Introductionmentioning
confidence: 91%